The articulation between the extended (5-year) and mainstream (4-year) programmes in Engineering at the University of Cape Town: Reflections and possibilities - Pearce, Howard; Campbell, Anita; Craig, Tracy; le Roux, Pierre; Nathoo, Kalpana; Vicatos, Evelyn (South African Journal of Higher Education, 2016)
Academic support and development in South Africa has been through a number of phases since the earlier 1980’s. The schooling system in 2013 is still struggling to deliver high quality education to all students and frequent changes to the school curriculum have created some frustration for universities. The national need for good engineering graduates is dire and universities are under pressure to produce more graduates and to increase the graduation rate. Universities must face the resulting challenges head-on and academic support will have to remain a crucial component of engineering programmes. Most academic support assists students with the transition from school to university. We argue that there is an important role for more of a presence of academic development practitioners in the transition from first year into second year as well as the need for greater influence in the engineering courses of the second and third years. The form of this influence would vary but might include working with staff on pedagogy, delivery of conceptually difficult material and assessment.